Satisfaction with and Self Confidence in Nursing care for Pediatric Patients with Heart Failure among Nursing Students after Attending High Fidelity Simulation - Buadong, Dongruethai; Granger, Jumpee; Punyoo, Jiraporn; Jongaramraung, Jongjai (Nursing Research and Innovation Journal, 2021)
Nursing education is essential to improve the quality of nursing learning.The mixed-method study approach consisting of a quantitative and qualitative design,was used to assess the satisfaction with learning outcomes and self-confidence in caring for pediatric patients with heart failure by using high fidelity simulation-based learning.Purposive sampling was used to recruit the participants, who were the third-year students of Ramathibodi School of Nursing and currently experienced high fidelity simulationbased learning. In the quantitative design, 55 nursing students participated in the study.A questionnaire was used to collect data on satisfaction with and self-confidence in nursing care after attending the high fidelity simulation. The quantitative data were analyzed with descriptive statistics. For the qualitative design, from the 55 students, 30 participants were specifically selected. The qualitative data collected from focus group interviews were then analyzed by content analysis. The results demonstrated that nursing students who experienced high fidelity simulation-based learning had a high to the highest level of satisfaction with and self-confidence in caring for pediatric patients with heart failure. Also, from the focus group, the students were satisfied with the high fidelity simulation and excited to learn about nursing care for pediatric patients with complex symptoms. They had practiced in applying theoretical knowledge and experience in nursing care for pediatric patients. Therefore, high fidelity simulation-based learning should be considered to develop the teaching and learning strategies for nursing students. Keywords: High fidelity simulation, Pediatric nursing, Satisfaction, Self-confidence, Nursing students